2023
DOI: 10.1021/acs.jpcb.2c08834
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Alkyl Ethoxylate Surfactants in a Dissipative Particle Dynamics Model

Abstract: We present a dissipative particle dynamics (DPD) model capable of capturing the liquid state phase behavior of nonionic surfactants from the alkyl ethoxylate (C n E m ) family. The model is based upon our recent work [Anderson et al. J. Chem. Phys. 2017 , 147 , 094503] but adopts tighter control of the molecular structure by setting the bond angles with guidance from molecular dynamics simulations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Hereafter we shall, for the most part, express elapsed times in DPD time-units. One DPD time-unit corresponds to ≈ 50 ps of real elapsed time, according to previously reported mappings based on matching diffusion coefficients (Fraaije et al, 2018;Anderson et al, 2023). Hence the adopted DPD time-step of 0.01 DPD time-units corresponds to ≈ 0.5 ps.…”
Section: Simulation and Analysis Detailsmentioning
confidence: 89%
See 3 more Smart Citations
“…Hereafter we shall, for the most part, express elapsed times in DPD time-units. One DPD time-unit corresponds to ≈ 50 ps of real elapsed time, according to previously reported mappings based on matching diffusion coefficients (Fraaije et al, 2018;Anderson et al, 2023). Hence the adopted DPD time-step of 0.01 DPD time-units corresponds to ≈ 0.5 ps.…”
Section: Simulation and Analysis Detailsmentioning
confidence: 89%
“…• The first is computational efficiency. We have demonstrated in our previous work (Anderson et al, 2023) that equilibration of micelle structures can take a very large simulation time (at least 10-40 million time-steps in the case presented in the cited literature). Whilst it is technically feasible to simulate such long time-scales given enough resources, to be of practical use it is of our view that the computational screening protocols ought to be more cost efficient and less time consuming than the alternative of running the laboratory trials.…”
Section: Simulation and Analysis Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other DPD studies have reported on the simulated properties of micelles. 20,21,37,[52][53][54][55][56][57][58][59] An important property in the development of surfactant-based formulated products is rheology, which influences a range of behaviors, from the ability of a product to flow from a bottle, the cleaning ability, to sensory interactions. The rheology of a formulation is strongly influenced by the nature of the self-assembled micellar structures present in it, in particular the presence of WLMs.…”
Section: Introductionmentioning
confidence: 99%